Insomnia complaints in lean patients with obstructive sleep apnea negatively affect positive airway pressure treatment adherence. (15th December 2016) - Eysteinsdottir, Bjorg; Gislason, Thorarinn; Pack, Allan I.; Benediktsdottir, Bryndís; Arnardottir, Erna S.; Kuna, Samuel T.; Björnsdottir, Erla
Summary: The objective of this study was to evaluate the determinants of long‐term adherence to positive airway pressure treatment among patients with obstructive sleep apnea, with special emphasis on patients who stop positive airway pressure treatment within 1 year. This is a prospective long‐term follow‐up of subjects in the Icelandic Sleep Apnea Cohort who were diagnosed with obstructive sleep apnea between 2005 and 2009, and started on positive airway pressure treatment. In October 2014, positive airway pressure adherence was obtained by systematically evaluating available clinical files ( n  = 796; 644 males, 152 females) with moderate to severe obstructive sleep apnea (apnea–hypopnea index ≥15 events per h). The mean follow‐up time was 6.7 ± 1.2 years. In total, 123 subjects (15.5%) returned their positive airway pressure device within the first year, 170 (21.4%) returned it later and 503 (63.2%) were still using positive airway pressure. The quitters within the first year had lower body mass index, milder obstructive sleep apnea, less sleepiness, and more often had symptoms of initial and late insomnia compared with long‐term positive airway pressure users at baseline. Both initial and late insomnia were after adjustment still significantly associated with being an early quitter among subjects with body mass index <30 kg m −2, but not among those with body mass index ≥30 kg m −2 . The prevalence of early quitters decreased significantly during the study period (2005–2009). Almost two‐thirds of patients with moderate to severe obstructive sleep apnea are positive airway pressure users after 7 years. Obesity level, obstructive sleep apnea severity and daytime sleepiness are important determinants of long‐term adherence. Symptoms of initial and late insomnia are associated with early quitting on positive airway pressure among non‐obese subjects.